The Relationship between Defending the State and National Character in Technological Development for the Millennial Generation During the COVID-19 Pandemic - Ester Nataliana; Yusnaldi Yusnaldi; Bayu Asih Yulianto; Pujo Widodo; Herlina Juni Risma Saragih; Panji Suwarno (IJRAEL: International Journal of Religion Education and Law, 2023)
Background: We know that the whole world is facing the same problem, namely the COVID-19 pandemic, including Indonesia. The Indonesian government has made every effort to reduce the pace of the COVID-19 pandemic by establishing policies and regulations such as implementing health protocols, and others. Covid-19 is a non-natural disaster that affects all aspects of life including the nation's character. The younger generation or those who are known as millennials as a determinant of the nation's character have an important role during the Covid-19 pandemic. The problem at this time is that millennials live in a modern and instant era that shapes them to be free, individualistic, and active in the field of technology. This has caused the millennial generation to start forgetting their love for the Motherland and Defending the Country. Methods: The method used in this research is descriptive qualitative and the human instrument is the researcher. A descriptive qualitative method in the form of analyzing and drawing conclusions using various sources of literature. Results: In times of peace and war, young intellectuals as the national guard in non-military defense have a crucial role as potential agents of change in shaping the character and character of the nation. The serious challenges faced by the younger generation must also be addressed by maintaining a balance between intellectual intelligence and emotional intelligence as well as spiritual intelligence. It is hoped that the balance of these three factors will manifest the behavior of young people who always uphold morals and ethics of honesty and nationality. This ability is a form of defending the country on a fine spectrum that needs to be carried out by young people in times of peace. From the perspective of national defense, it is precisely this role of defending the country in the soft spectrum that will determine the quality of the nation's defense and resilience in the future. The toughness and tenacity and ability of the nation to develop the potential of national strength to become a solid state defense force need to be built on the values of nationalism and defense of the country. From the perspective of national resilience, these three basic elements are prerequisites that must be fostered early, continuously, integrated and sustainable. Intellectual intelligence which is a great potential possessed by young people must be able to be developed in a balanced way with emotional intelligence, moral intelligence, and spiritual intelligence. During the Covid-19 pandemic, it turned out that the millennial generation showed high concern and made good contributions as a form of defending the country to maintain national resilience and support the Indonesian government in preventing and handling unexpected events such as Covid-19. Conclusion: The existence of social media as a form of technological progress can be used to hold fundraising events which will later be given to underprivileged communities affected by Covid-19 and medical personnel who lack PPE (personal protective equipment). With the urgency of Indonesia's current situation, the younger generation is required to care about using technology as best as possible in an effort to defend the country which is carried out to help the government and show love for the motherland, harmonious relations between the government and its people, and awareness of the obligations of the nation and state.